2021
DOI: 10.1080/10942912.2020.1858862
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ultrasound assisted nucleation during freezing and its application in food freezing process

Abstract: Ultrasound assisted freezing (UAF) is a common and remarkable technology of food preservation to conserve the sensory characteristics and nutritional value. The propagation of ultrasound in a medium generates various physical and chemical effects and these effects have been harnessed to improve the efficiency of food freezing. This review provides an overview of recent developments related to the mechanism, influencing factors, equipment of UAF. The applications of high intensity ultrasound to improve the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…There was no significant difference in the pre-cooling time found between samples with IF and UIF treatments ( p > 0.05) during the pre-cooling phase, without the application of ultrasound ( Table 1 ). In the phase change stage, most of the water would crystallize, so this stage can directly determine the freezing quality of the product ( 32 ). As the ultrasonic power became higher, the phase transition time increased and then diminished, which was consistent with the results of the total freezing time.…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference in the pre-cooling time found between samples with IF and UIF treatments ( p > 0.05) during the pre-cooling phase, without the application of ultrasound ( Table 1 ). In the phase change stage, most of the water would crystallize, so this stage can directly determine the freezing quality of the product ( 32 ). As the ultrasonic power became higher, the phase transition time increased and then diminished, which was consistent with the results of the total freezing time.…”
Section: Resultsmentioning
confidence: 99%
“…The collapse of the cell wall is the first step in ultrasonic disruption of yeast cells, followed by low-intensity damage to the cell membrane. The above findings can create new possibilities for cell disruption and microorganism inactivation [ 38 ]. The same study suggested that high temperatures disrupt cell walls and thermally adhere to intracellular proteins.…”
Section: Ultrasonic Wavesmentioning
confidence: 99%
“…An ultrasound is a high-frequency elastic wave propagating through a medium. Cavitation occurs when the wave energy reaches a threshold (Ma et al, 2021b). The propagation of acoustic waves between positive and negative pressure causes a series of non-linear processes, such as expansion, compression, collapse, and oscillation of tiny bubbles (Alarcon-Rojo et al, 2019).…”
Section: Meat Structure and Mechanism Of Ultrasound-assisted Tenderiz...mentioning
confidence: 99%